2017
DOI: 10.1021/acsnano.7b03942
|View full text |Cite
|
Sign up to set email alerts
|

Silicene Flowers: A Dual Stabilized Silicon Building Block for High-Performance Lithium Battery Anodes

Abstract: Nanostructuring is a transformative way to improve the structure stability of high capacity silicon for lithium batteries. Yet, the interface instability issue remains and even propagates in the existing nanostructured silicon building blocks. Here we demonstrate an intrinsically dual stabilized silicon building block, namely silicene flowers, to simultaneously address the structure and interface stability issues. These original Si building blocks as lithium battery anodes exhibit extraordinary combined perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
105
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 137 publications
(107 citation statements)
references
References 58 publications
2
105
0
Order By: Relevance
“…To date, various 2D anode materials like titanium oxides, transition metal oxides, metal phosphides/sulfides/nitrides, have been extensively applied for LIBs. Among these 2D anode materials, 2D silicon have received intense attention as one of the most promising high‐capacity electrodes for the next‐generation LIBs due to its ultrahigh theoretical lithium storage capacity, faster Li diffusion rates, and relatively low discharge potential, as well as lower diffusion energy barrier (0.23 eV) of lithium ions . Despite these impressive benefits in 2D Si anodes, there remains a crucial challenge to realize its large‐scale preparation using low‐cost method.…”
Section: Introductionmentioning
confidence: 99%
“…To date, various 2D anode materials like titanium oxides, transition metal oxides, metal phosphides/sulfides/nitrides, have been extensively applied for LIBs. Among these 2D anode materials, 2D silicon have received intense attention as one of the most promising high‐capacity electrodes for the next‐generation LIBs due to its ultrahigh theoretical lithium storage capacity, faster Li diffusion rates, and relatively low discharge potential, as well as lower diffusion energy barrier (0.23 eV) of lithium ions . Despite these impressive benefits in 2D Si anodes, there remains a crucial challenge to realize its large‐scale preparation using low‐cost method.…”
Section: Introductionmentioning
confidence: 99%
“…Unless otherwise specified, the capacity values reported were calculated on the basis of the total weight of the tested electrodes. It can be observed that the mSi@OG@RGO shows similar cyclic voltammetry (CV) peaks (Figure a and Figure S6, Supporting Information) and galvanostatic voltage profiles (Figure b) to those of other silicon anodes . Figure c displays the rate performance of the mSi@OG@RGO and the mSi@RGO control sample, demonstrating high rate capability of the mSi@OG@RGO.…”
mentioning
confidence: 78%
“…To address this electrode formulation failure and advance the use of silicon as the LIB anode material, various nanostructured silicon building blocks (e.g., nanoparticles, nanowires, nanotubes, and nanosheets) have been engaged, considering that structural fracture can be avoided, and electrical disconnection can be alleviated when decreasing the material feature size to the nanoscale . In particular, a wide range of materials design concepts have been further developed to construct void‐involved silicon/carbon nanostructures such as point‐to‐point contacted yolk–shell and line‐to‐line contacted wire‐in‐tube Si–C nanohybrids, so as to minimize destruction of the electrode architecture by the volume change of individual material particles as well as render a stable SEI on the surface of individual material particles thereby restraining the degradation of electron/lithium ion transport paths from/to silicon.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Silica fume and magnesium (Mg) powder as starting materials were mixed together and then heated to a high temperature to synthesize silicene (Figure 4). 73 As‐prepared silicene flowers were further employed as lithium battery anodes, which exhibited extraordinary electrochemical performance. The feasibility of this technique endows great potential for the preparation of silicene.…”
Section: Synthesis and Structures Of 2d Group‐iv Materialsmentioning
confidence: 99%